Development of a biorelevant methodology for drug release in the mouth - Ali, Joseph (2020)
The oral route is the most popular and convenient route for drug administration. There are a growing number of alternative solid oral dosage forms that have been developed for more specialised drug delivery compared to monolithic solid oral dosage forms. Alternative formulations can aim to promote or inhibit the release of a drug within the oral cavity, and therefore are directly linked to processing within the mouth. Alternative oral formulations such as orally disintegrating tablets (ODTs) can be used to combat dysphagia, as the dosage form is designed to disintegrate in saliva within relatively short time frame. Polymer coated taste-masked multiparticulates can be used to increase the palatability of the dosage form by reducing the contact between the poor tasting active pharmaceutical ingredient (API) and taste receptor cells. In vitro dissolution testing can be employed to elucidate the performance of these alternative oral formulations within the oral cavity by quantifying release of the API in biorelevant oral cavity conditions. This could provide a robust analytical approach to assess formulation design at earlier stages of drug product development. A vast number of dissolution methodologies have been suggested for oral cavity testing, however, there is little agreement between methods, and a lack of biorelevance. For oral cavity dissolution methods to be able to predict in vivo drug release, the method must account for biorelevant processing of the dosage form in the mouth. The dissolution media should mimic the relevant properties of human saliva in dissolution testing in the oral cavity. Recently, pH, buffer capacity, surface tension, viscosity and flow rate of both unstimulated (US) and stimulated (SS) human saliva was characterised. This characterisation of human saliva provided a platform of reference for the future development of simulated salivary fluids (SSFs). As a result, biorelevant SSFs with similar physicochemical properties to human saliva have been developed to use within oral cavity dissolution studies. This work demonstrated how human saliva dissolution can be used to aid formulation design of felodipine ODTs (Chapter 3). Additionally, compendial dissolution methods showed to greatly overpredict drug release compared to saliva-based dissolution, highlighting the importance of biorelevance for in vitro predictability (Chapter 3). Whilst human saliva is the most relevant fluid to use for oral cavity dissolution studies, the availability of ex vivo biological fluid is restricted. Therefore, a biorelevant simulated salivary fluid has been developed as a surrogate for human saliva for dissolution assessment. There are limited tools available for the assessment of particulate taste-masked formulations in a preclinical setting. The current preclinical rodent in vivo taste evaluation methods are designed for the assessment of liquid formulations. Since these taste evaluation methods are designed for liquid formulations an investigation was required to ascertain whether these rodent models can be adapted for particulate based taste-masked formulations. However, the characteristics and dissolution of APIs in rat saliva was found to be significantly different from human saliva (Chapter 4). Therefore, the rodent taste evaluation models would not likely be representative of the taste response from human taste panels for particulate-based taste-masked formulations. This lack of biorelevance further supports the need for a biorelevant oral cavity dissolution test method. In this thesis, for the first time, artificial saliva preparations provided equivalent dissolution of three unrelated APIs to human salivary fluid (Chapter 5). The biorelevant SSFs were then successfully applied to a flow-through dissolution apparatus to mimic the physiology of the oral cavity (Chapter 6). The use of the oral cavity model was successful in assessing drug release from polymer coated taste-masked multiparticulate formulations (Chapter 6). Additionally, the flow-through oral cavity dissolution model was used to assess the applicability of nanoprecipitation as a novel taste-masking strategy (Chapter 7). Thus, the developed oral cavity dissolution media can be used in early stages of drug discovery and development. Specifically, to aid formulation design and optimisation for several different formulation approaches where understanding the release in the oral cavity is important.